Design of Distillation Column Control Systems - Luyben, William L.; Buckley, P.; Shunta, J. P. (Butterworth-Heinemann [Imprint] San Diego : Elsevier Science & Technology Books, 1985)
Annotation A distillation column is both multivariable and nonlinear - and it consumes immense quantities of energy. Yet, despite the desigh challenges it presents, it is still the most popular unit operation for refining in industrial plants today. Much has been published on the subject of distillation column design, but much remains to be explained. That is why this book is unique. In a departure from the more traditional empirical and theoretical approaches, it introduced the reader to the practical realm, by presenting quantitative design techniques that have been demonstrated to be useful and valid over the course of hundreds of actual applications. The book is divided into three main parts. Part I, an introduction, presents an industrial perspective of control objectives. It discusses briefly the relationship between column design features and column controllability. It thus provides a short refresher course for chemical engineers and background for those trained in other branches of engineering. Part II, Concepts and Configurations, discusses column overhead and base arrangements, typical control schemes, and some hardware considerations. Part III is dedicated to quantitative design. Mathematical models are presented for pressure and differential pressure controls, liquid level control, and composition control of binary distillation. Emphasis on topics of primary interest to the control engineer Essentially nonmathematical treatment Ideal for those involved in troubleshooting existing columns as well to design engineers
Includes Index.
Scholarly & Professional
Keywords: Chemical Process Control